Exploring the Benefits of Mindfulness-Based Stress Reduction Intervention in Breast Cancer: Outcomes and Perspectives - Ernesto Cotonieto Martínez (Mexican Journal of Medical Research ICSA)
Breast cancer represents a significant public health challenge, requiring treatment approaches that address psychosocial aspects to improve the quality of life for both patients and survivors. This review aims to explore the diverse effects of mindfulness-based interventions on outcomes in breast cancer patients and survivors. Despite the challenges in integrating MBIs into conventional oncological care, their importance cannot be underestimated. The findings highlight the considerable potential of MBIs in enhancing the well-being of individuals affected by breast cancer.